Day 3 Wed, March 23, 2016 2016
DOI: 10.2118/179775-ms
|View full text |Cite
|
Sign up to set email alerts
|

Production and Application of Schizophyllan in Microbial Enhanced Heavy Oil Recovery

Abstract: Generally partially hydrolyzed polyacrylamides (HPAM) are used worldwide for polymer-based oil recovery processes. However there aree some problems associated with HPAM applications such as, treatment of produced water, oil-water separation and toxicity issues associated with degradation products of HPAM. Schizophyllan biopolymer is biodegradable and environmental friendly alternative to chemical polymers used for EOR applications. In present work we studied the schizophyllan production by fungi Schizophyllum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…None of the media showed much increase in the viscosities even after 72 h, and the viscosities varied between 1.3 and 1.5 mPa s, for both abiotic controls and experimental samples. The viscosities of some of the biopolymers are reported to be in the range of 43–21535 cP (Joshi et al, 2016). Hence, it was concluded that this isolate B. licheniformis W16 produced only biosurfactant and not biopolymer, under tested environmental conditions in these nine minimal media.…”
Section: Resultsmentioning
confidence: 99%
“…None of the media showed much increase in the viscosities even after 72 h, and the viscosities varied between 1.3 and 1.5 mPa s, for both abiotic controls and experimental samples. The viscosities of some of the biopolymers are reported to be in the range of 43–21535 cP (Joshi et al, 2016). Hence, it was concluded that this isolate B. licheniformis W16 produced only biosurfactant and not biopolymer, under tested environmental conditions in these nine minimal media.…”
Section: Resultsmentioning
confidence: 99%
“…A variety of microorganisms produce biopolymers useful for application in MEOR, including species belonging to the genera Alcaligenes, Aureobasidium, Bacillus, Leuconostoc, Pseudomonas, Sphingomonas and Xanthomonas [1,4,12,[20][21][22][23][24]. Among these biopolymers, xanthan gum, produced by the bacterium Xanthomonas campestris, stands out.…”
Section: Introductionmentioning
confidence: 99%
“…This behavior is primarily attributed to the increased molecular mobility and reduced intermolecular forces within the natural polymer chains. , Consequently, the viscosity of the polymer decreases as it becomes easier for the chains to slide past each other. The viscosity of polymer solutions with polysaccharides depends on various parameters such as molecule structure, concentration, and the presence of other substances.…”
Section: Resultsmentioning
confidence: 99%
“…These results could be compared with 20% of additional oil recovery after 1 PV of C. olitorius, as for the experiment conducted by Joshi et al (2016) six times more polymer solution was used …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation